The influence of endogenous and exogenous sex hormones on systemic lupus erythematosus in pre- and postmenopausal women - Grygiel-Górniak, Bogna; Puszczewicz, Mariusz Jacek (Menopause Review/Przegląd Menopauzalny, 2014)
Systemic lupus erythematosus (SLE or lupus) is a chronic inflammatory disease that occurs mainly in women. Typically, symptoms appear within the first few years of adolescence, but currently an increase can be observed in the percentage of postmenopausal women with this condition. This is possibly due to the sophisticated treatment of the disease, which significantly improves the survival curve and prognosis. Genetic and environmental factors are involved in the development of SLE. Both regulation of the immune system and the activity of this disease are influenced by a variety of hormones, including: 17-estradiol, testosterone, prolactin, progesterone and dehydroepiandrosterone (DHEA). Early menarche, menstrual cyclicity, the total number of years characterized by ovulatory cycles and early menopause are correlated with the development of SLE. Because of the health risks, attempts are increasingly being made to evaluate the impact of exogenous hormones (especially those applied exogenously) on the course of SLE. In particular, the role of estrogens is being highlighted, either endo- or exogenous, including oral contraceptives (OC), therapy used in the treatment of infertility, and hormonal replacement therapy (HRT). The purpose of this manuscript is the revision of the literature concerning the impact of both endo- and exogenous estrogens on the development of lupus, inducement of flares and any possible complications.